Intraoperative Fluid Management Correlates with Intraoperative Complications in Cesarean Section: A Prospective Clinical Trial - Humianto, Michael; Marilaeta Cindryani; Tjokorda Gde Agung Senapathi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: This study focused on perioperative fluid administration in pregnant women undergoing a caesarean section (CS) by comparing liberal and non-liberal fluid administration in a multicentre setting across various Hospitals in the Bali province and its surrounding areas. Methods: Sampling was conducted using a total sampling method. All patients meeting the inclusion criteria were included in this study. A total of 310 samples of pregnant patients undergoing CS surgery in various operating rooms across hospitals in the Bali province and surrounding areas were obtained during the period of January to December 2022. The fluid administration strategy was divided into two types: liberal and non-liberal. Data analysis was performed using the Chi-square test with the correlation test of the contingency coefficient. Results: The results showed that liberal fluid administration significantly increased complications in the operating room for pregnant patients undergoing cesarean section (p<0.001; r=0.305; OR 6.22) but not in the recovery room or postoperative hospital ward. Conclusion: Liberal fluid administration could significantly increase complications in the operating room for pregnant patients undergoing cesarean section but not in the postoperative period.